Congenital diaphragmatic hernia: Late presentation - Vajravel, Logavengatesh; Raman, Radhika (Indian Journal of Case Reports, 2019)
Late presentation of congenital diaphragmatic hernia (CDH) as an emergency is uncommon. Here, we report the case series of 3 patientswith CDH presenting to the emergency with similar complaints and had radiological features suggestive of hydropneumothorax andpleural effusion. Following emergency surgical intervention, the outcome was good. We highlight the radiological feature in CDH thatcan be misleading as it can mimic acute respiratory conditions such as pleural effusion or pneumonia.